Editing Rhythm in Building Dramatic Tension in the Film Qodrat 2 - Sutan Muhammad Aqil; Wahyu Nova Riski (KINEMA: Jurnal Komunikasi dan Penyiaran, 2026)
This study examines how editing rhythm builds dramatic tension in the film Qodrat 2. The research focuses on the use of editing rhythm in shaping the dynamics of tension and release in several scenes that show significant changes in conflict. This study employs a descriptive qualitative method using Karen Pearlman's editing rhythm approach, particularly through the aspects of pacing, timing, and trajectory phrasing. The research data were obtained through film observation, documentation of the analyzed scenes, timecode recording, literature review, and interviews with the assistant editor of Qodrat 2. The results indicate that editing rhythm in Qodrat 2 plays a role in building, sustaining, and releasing tension through changes in shot duration, the speed of shot transitions, movement, and the development of dramatic energy within scenes. Pacing is the most dominant aspect in building tension, particularly through the acceleration and slowing down of rhythm in accordance with the progression of conflict. Meanwhile, timing plays a role in creating release through shot placement and longer shot durations after the conflict reaches its peak. Additionally, trajectory phrasing reveals the rising and falling pattern of rhythm in shaping the audience's emotional experience. Thus, editing rhythm in Qodrat 2 not only serves to build visual continuity but also functions as a dramatic element in building tension and eliciting the audience's emotional response.